A new genus and a new species in the sea cucumber subfamily Colochirinae (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae) in the Mediterranean Sea - Mjobo, Sifiso; Thandar, Ahmed S. (Zootaxa, 2016)
A new genus Hemiocnus is here erected to accommodate the Mediterranean dendrochirotid sea cucumber Cladodactyla syracusana Grube, currently classified, with some doubt, in the cucumariid genus Pseudocnella. At the same time a new cucumariid species, Hemiocnus rubrobrunneus, is described from some Tunisian material, misidentified as Pseudocnella syracusana (Grube), received from the United States National Museum. The new genus appears most closely related to Pseudocnella than to any other genus within the Colochirinae. Although its body wall ossicles resemble those of Pseudocnella spp. it differs in that the two ventral-most tentacles are reduced and in the presence of rosettes in the tentacles. P. syracusana also cannot be classified in Ocnus because of the presence of multi-layered, fir-cone shaped plates in the body wall, often with one end denticulate; such ossicles are lacking in the type species of the latter genus. The new species, Hemiocnus rubrobrunneus, on the other hand, shows some resemblance to H. syracusanus in its characteristic buttons and incomplete baskets, differing in its softer body wall, lack of fir-cone-shaped plates and in the presence of rosettes and complete baskets in the body wall. There are also some resemblances of the new species to the Mediterranean species of Ocnus viz. O. brunneus, O. planci and O. lacteus, but the soft nature of the body wall, shallow quadrilocular instead of deep trilocular baskets, and the presence of large knobbed plates in the anal region precludes its inclusion in this genus.